Edukasi Pentingnya Pendidikan bagi Anak di Dusun Salut Kendal - Patty, Elyakim Nova Supriyedi; Anggrawan, Anthony; Satria, Christofer; Wardhana, Helna; Susilowati, Dyah; Iriyani, Sri Astuti; Rahim, Abdul (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The purpose of this activity is: to provide counseling, socialization, and understanding of the importance of education for children given to the people of Salut Kendal Hamlet, Salut Village, Kayangan District, North Lombok Regency. the socialization activity was a collaboration between the Non-Governmental Organization Selaksa Sejahtera Foundation (YASERA) Mataram and Bumigora University. Participants were residents of Salut Kendal Hamlet, 40 people out of the planned 70 people carried out in one day. The method of implementing this service is the preparation and socialization stage which is packaged in the form of a workshop at the location of the savings for life family meeting. The results of the implementation of Community Service show that the level of understanding of community service participants is more aware of the importance of education for children in efforts to fulfill children's rights and prevent child marriage and to build parents' commitment to send their children at least to high school graduation.